TINGKAT PARTISIPASI MASYARAKAT DALAM PENGGUNAAN APLIKASI WEB DESA AKA-AKAE KECAMATAN WATANG SIDENRENG KEBUPATEN SIDENRENG RAPPANG - Kamiati Kamiati; Sapri Sapri; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
Research objectives To determine the level of community participation in the use of web applications in Aka - Akae Village, to find out the factors that influence the level of community participation in the use of web applications in Aka - Akae Village. The population of this study was 499KK, while the research sample was 83 people. The data collection techniques used in this research are (1) observation, (2) decision study, (3) questionnaire, while using scalalicert data analysis technique. The collected data were then analyzed using a frequency table and using the SPSS 2.1 application. The results of the research on the level of community participation on the use of web applications in the Aka-Akae village, Watang Sidenreng district, were included in the